Levels of neuroactive steroids are elevated in those who develop first-onset depression early in pregnancy - Wenzel, Elizabeth S.; Barone, Jordan C.; Eisenlohr-Moul, Tory A.; Alvernaz, Suzanne; Peñalver Bernabé, Beatriz; Spiro Santovito, Luca; Gdyana, Ibrahim M. M.; Pinna, Graziano; Maki, Pauline M. (Frontiers in Psychiatry, 2025)
BackgroundAllopregnanolone (ALLO) plays a key role in the pathogenesis of postpartum depression. However, ALLO levels have been variably associated with depression during pregnancy. It is unknown if a pre-pregnancy history of major depressive disorder (MDD), which is associated with blunted neurosteroidogenesis, and timing of perinatal depression (PND) may influence the association between neuroactive steroids (NAS) and PND.ObjectiveTo investigate differences in ALLO and other NAS levels during the first (T1) and second (T2) trimesters based on pre-pregnancy history of MDD and current PND.MethodsParticipants completed a diagnostic test of depression, blood samples and mental health history. Ninety-eight participants contributed data in T1 and 93 in T2. Levels of ALLO, pregnanolone (PA), isoallopregnanolone (ISO), epipregnanolone (EPI), and progesterone (P4) were quantified using gas chromatography-mass spectrometry. Analyses of covariance with pairwise comparisons predicted NAS levels from categorized groups of those with: 1) no history of MDD and no PND (never depressed), 2) a history of MDD but no PND (pre-pregnancy depression), 3) a history of MDD and current PND (recurrent depression), and 4) no history of MDD but current PND (perinatal-emergent depression).ResultsAcross groups, there were marginally significant differences in T1 ALLO (p=.05) and ISO levels (p=.05). T1 ALLO levels were higher in the perinatal-emergent versus never depressed (p=.007) and recurrent depression (p=.05) groups. ISO levels were higher in the perinatal-emergent versus recurrent depression (p=.02) and never depressed (p=.03) groups. In T2, there were significant differences in PA levels (p=.04) and marginally significant differences in ALLO (p=.07) and ISO levels (p=.09). ALLO levels were higher in the perinatal-emergent versus recurrent depression group (p=.05), and in the never depressed (p=.05) and pre-pregnancy depression groups (p=.04) compared to recurrent depression. PA levels were higher in the perinatal-emergent depression versus never depressed (p=.02) and recurrent depression (p=.01) groups, and ISO levels were higher in the perinatal-emergent depression versus never depressed (p=.03) and recurrent depression (p=.07) groups.ConclusionsThese results suggest differing NAS-related mechanisms of pathogenesis across clinical phenotypes based on pre-pregnancy history of MDD and timing of PND onset. Future research should account for these factors when investigating NAS and PND.